Strengthening Early Childhood Social-Emotional Character through STEAM-Based Learning - Thea Yuliana Anjari; Tita Sapriyanti; Aisyah Oktavia Siregar; Arnita Fitri; Hera Dwi Kusuma Wardani (Journal of English Language and Education, 2026)
This study aims to analyze the effect of STEAM-based learning on strengthening the social-emotional character of early childhood. Various studies have examined the application of STEAM (Science, Technology, Engineering, Arts, and Mathematics) learning in early childhood education, but the majority still focus on the development of cognitive aspects, creativity, and critical thinking skills. Research that specifically integrates the STEAM approach with strengthening social-emotional character, especially on indicators of cooperation, empathy, emotional control, and social communication, is still very limited, and there is minimal empirical evidence based on experimental designs comparing its effectiveness with conventional learning. The study subjects were 30 children aged 5–6 years who were divided into an experimental class and a control class. Data were collected through observations using a Likert scale instrument based on four social-emotional indicators. The results showed that the experimental class experienced higher improvements than the control class, with a gain value of 1.35 in the experimental class and 0.70 in the control class. Statistical tests showed a significant difference between the two groups. These findings indicate that STEAM-based learning is effective in improving children's social-emotional character through interactive, collaborative, and experience-based activities. Thus, this study fills a research gap by providing empirical evidence that STEAM integration in learning not only contributes to cognitive aspects but also significantly strengthens the social-emotional character of early childhood.